Differential Recruitment of Anterior Intraparietal Sulcus and Superior Parietal Lobule during Visually Guided Grasping Revealed by Electrical Neuroimaging - Tunik, Eugene (J Neurosci, 2008)
Dorsal parietal cortex is required for visually guided prehension. Transcranial magnetic stimulation to either the anterior intraparietal sulcus (aIPS) or superior parietal lobule (SPL) disrupts on-line adaptive adjustments of grasp when objects are perturbed. We used high-density electroencephalography during grasping to determine the relative timing of these two areas and to test whether the temporal contribution of each site would change when the task goal was perturbed. During object grasping with the right-hand, two distinct evoked responses were present over the 50–100 and 100–200 ms periods after movement onset. Distributed linear source estimation of these scalp potentials localized left lateralized sources, first in the aIPS and then the SPL. The duration of the response from the aIPS area was longer when there was an object perturbation. Initiation of a corrective movement coincided with activation in SPL. These data support a two-stage process: the integration of target goal and an emerging action plan within aIPS and subsequent on-line adjustments within SPL.